Ru complexes of Hoveyda-Grubbs type immobilized on lamellar zeolites: activity in olefin metathesis reactions - Balcar, Hynek; Žilková, Naděžda; Kubů, Martin; Mazur, Michal; Bastl, Zdeněk; Čejka, Jiří (Beilstein journal of organic chemistry, 2015)
Hoveyda-Grubbs type catalysts with cationic tags on NHC ligands were linker-free immobilized on the surface of lamellar zeolitic supports (MCM-22, MCM-56, MCM-36) and on mesoporous molecular sieves SBA-15. The activity of prepared hybrid catalysts was tested in olefin metathesis reactions: the activity in ring-closing metathesis of citronellene and N,N-diallyltrifluoroacetamide decreased in the order of support MCM-22 ≈ MCM-56 > SBA-15 > MCM-36; the hybrid catalyst based on SBA-15 was found the most active in self-metathesis of methyl oleate. All catalysts were reusable and exhibited low Ru leaching (<1% of Ru content). XPS analysis revealed that during immobilization ion exchange between Hoveyda-Grubbs type catalyst and zeolitic support occurred in the case of Cl(-) counter anion; in contrast, PF6 (-) counter anion underwent partial decomposition.
Keywords: non-covalent immobilization; hybrid catalysts; olefin metathesis; lamellar zeolites; Hoveyda–Grubbs type catalyst